2015
DOI: 10.1177/070674371506001203
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice: Separating Science from Pseudoscience

Abstract: Evidence-based practice (EBP) requires that clinicians be guided by the best available evidence. In this article, we address the impact of science and pseudoscience on psychotherapy in psychiatric practice. We describe the key principles of evidence-based intervention. We describe pseudoscience and provide illustrative examples of popular intervention practices that have not been abandoned, despite evidence that they are not efficacious and may be harmful. We distinguish efficacy from effectiveness, and descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…What has been intimated by the extant empirical literature is that the CPGs covered in this paper remain empirically cited (eg, see Saddichha and Chaturvedi and Lee and Hunsley). What the preliminary empirical evidence suggests, at least among a large sample of 1878 Canadian physicians in active practice, is that 55% of them found that the consistency with what is customary or espoused in local practice was “most important” for them in rating whether they actually decide to adopt CPGs .…”
Section: Discussionsupporting
confidence: 55%
“…What has been intimated by the extant empirical literature is that the CPGs covered in this paper remain empirically cited (eg, see Saddichha and Chaturvedi and Lee and Hunsley). What the preliminary empirical evidence suggests, at least among a large sample of 1878 Canadian physicians in active practice, is that 55% of them found that the consistency with what is customary or espoused in local practice was “most important” for them in rating whether they actually decide to adopt CPGs .…”
Section: Discussionsupporting
confidence: 55%
“…This is reflected in guidelines for clozapine prescription [7, 8]: a 2014 review of clozapine prescription trends concludes that clozapine has consistently remained the gold standard for treatment-resistant schizophrenia, with all evidence-based guidelines recommending prescription “after failure of two adequate trials of two different antipsychotic agents” [9]. Recent variations have progressed from exclusively considering persistent positive symptoms to also incorporating persistent negative and cognitive symptoms [10, 11]; however positive symptoms remain a central focus as the main target of antipsychotics and the primary outcome in the early clozapine trials which defined treatment-resistance (see 2016 review highlighting role of positive symptoms [12]).…”
Section: Introductionmentioning
confidence: 99%
“…The aim was to provide objective data derived through scientific processes that could state without ambiguity what treatments were effective and for whom. The hope was to eventually develop a streamlined mental health care system wherein practitioners utilized the best evidence available to inform optimal interventions in order to yield “maximum returns” (Lee & Hunsley, , p. 535 [Dozois et al, ; Spring, ]).…”
Section: The Shift Toward the Objectifiablementioning
confidence: 99%